HUBUNGAN ANTARA MEROKOK DENGAN HEALTH-RELATED QUALITY OF LIFE (HRQOL) PADA MASYARAKAT DI DESA RUMOONG ATAS - Ruindungan, Putrinesia Kinanti; Manawan, Fridly (PHARMACON, 2025)
Ministry of Health continues to strive to stop smoking, where cigarettes have a huge impact not only in terms of health itself, but also have an impact on the socio-economic situation of the community. The aim of this study was to determine the relationship between smoking and health-related quality of life (HRQoL) in Rumoong Atas Village, South Minahasa Regency. This study was a descriptive analytic study with a cross-sectional design where data were collected prospectively using the Medical Outcome Short-Form 36 (SF-36) instrument. The data was then subjected to a correlation test using Kendall-Tau to determine the relationship between smoking and quality of life in the community in Rumoong Atas Village. The results showed that all domains were dominated by the good quality of life category and the test results using the Kendall-Tau correlation with a Sig. (2-Tailed) value of 0.285 and a Correlation Coefficient of 0.144, indicating that there was negatively relationship between smoking and quality of life.